Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's go through the process of factoring each of these differences of two cubes step-by-step.
### 1. Factoring [tex]\( 8x^3 - 27y^3 \)[/tex]
The general formula for the difference of cubes is:
[tex]\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \][/tex]
For [tex]\( 8x^3 - 27y^3 \)[/tex]:
- Here, [tex]\( a = 2x \)[/tex] and [tex]\( b = 3y \)[/tex].
- Therefore:
[tex]\[ 8x^3 - 27y^3 = (2x - 3y)((2x)^2 + (2x)(3y) + (3y)^2) \\ = (2x - 3y)(4x^2 + 6xy + 9y^2) \][/tex]
### 2. Factoring [tex]\( 16x^3 - 54y^3 \)[/tex]
First, factor out the common factor of 2:
[tex]\[ 16x^3 - 54y^3 = 2(8x^3 - 27y^3) \][/tex]
We have already factored [tex]\( 8x^3 - 27y^3 \)[/tex] from the first example:
[tex]\[ 8x^3 - 27y^3 = (2x - 3y)(4x^2 + 6xy + 9y^2) \][/tex]
Thus:
[tex]\[ 16x^3 - 54y^3 = 2(2x - 3y)(4x^2 + 6xy + 9y^2) \][/tex]
### 3. Factoring [tex]\( 27x^3 - 64y^3 \)[/tex]
Using the general formula again:
[tex]\[ a = 3x \text{ and } b = 4y \][/tex]
- Therefore:
[tex]\[ 27x^3 - 64y^3 = (3x - 4y)((3x)^2 + (3x)(4y) + (4y)^2) \\ = (3x - 4y)(9x^2 + 12xy + 16y^2) \][/tex]
### Matching each expression with its factored form:
[tex]\[ \begin{array}{ll} 8 x^3-27 y^3 & \rightarrow (2 x-3 y)\left(4 x^2+6 x y+9 y^2\right)\\ 16 x^3-54 y^3 & \rightarrow 2(2 x-3 y)\left(4 x^2+6 x y+9 y^2\right)\\ 27 x^3-64 y^3 & \rightarrow (3 x-4 y)\left(9 x^2+12 x y+16 y^2\right)\\ \end{array} \][/tex]
### 1. Factoring [tex]\( 8x^3 - 27y^3 \)[/tex]
The general formula for the difference of cubes is:
[tex]\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \][/tex]
For [tex]\( 8x^3 - 27y^3 \)[/tex]:
- Here, [tex]\( a = 2x \)[/tex] and [tex]\( b = 3y \)[/tex].
- Therefore:
[tex]\[ 8x^3 - 27y^3 = (2x - 3y)((2x)^2 + (2x)(3y) + (3y)^2) \\ = (2x - 3y)(4x^2 + 6xy + 9y^2) \][/tex]
### 2. Factoring [tex]\( 16x^3 - 54y^3 \)[/tex]
First, factor out the common factor of 2:
[tex]\[ 16x^3 - 54y^3 = 2(8x^3 - 27y^3) \][/tex]
We have already factored [tex]\( 8x^3 - 27y^3 \)[/tex] from the first example:
[tex]\[ 8x^3 - 27y^3 = (2x - 3y)(4x^2 + 6xy + 9y^2) \][/tex]
Thus:
[tex]\[ 16x^3 - 54y^3 = 2(2x - 3y)(4x^2 + 6xy + 9y^2) \][/tex]
### 3. Factoring [tex]\( 27x^3 - 64y^3 \)[/tex]
Using the general formula again:
[tex]\[ a = 3x \text{ and } b = 4y \][/tex]
- Therefore:
[tex]\[ 27x^3 - 64y^3 = (3x - 4y)((3x)^2 + (3x)(4y) + (4y)^2) \\ = (3x - 4y)(9x^2 + 12xy + 16y^2) \][/tex]
### Matching each expression with its factored form:
[tex]\[ \begin{array}{ll} 8 x^3-27 y^3 & \rightarrow (2 x-3 y)\left(4 x^2+6 x y+9 y^2\right)\\ 16 x^3-54 y^3 & \rightarrow 2(2 x-3 y)\left(4 x^2+6 x y+9 y^2\right)\\ 27 x^3-64 y^3 & \rightarrow (3 x-4 y)\left(9 x^2+12 x y+16 y^2\right)\\ \end{array} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.